Modelado de un sistema solar fotovoltaico para el colegio el bosque bilingüe UAN - Andrés Camilo, Zarate Mahecha (Universidad Antonio Nariño, 2023)
This research work comes up with the aim of studying the feasibility of a nonconventional energy system for “colegio el bosque bilingüe UAN”, this in order to achieve savings and efficient use of it, which looks to involve the educational community of the institution to work proactively and jointly from different academic approaches, the project was divided into three stages.